2007
DOI: 10.1371/journal.pone.0000832
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms within Novel Risk Loci for Type 2 Diabetes Determine β-Cell Function

Abstract: BackgroundType 2 diabetes arises when insulin resistance-induced compensatory insulin secretion exhausts. Insulin resistance and/or β-cell dysfunction result from the interaction of environmental factors (high-caloric diet and reduced physical activity) with a predisposing polygenic background. Very recently, genetic variations within four novel genetic loci (SLC30A8, HHEX, EXT2, and LOC387761) were reported to be more frequent in subjects with type 2 diabetes than in healthy controls. However, associations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
109
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(119 citation statements)
references
References 24 publications
7
109
3
Order By: Relevance
“…Remarkably, second-phase insulin secretion remained intact. Previously, several studies have investigated the effects of novel susceptibility loci on insulin secretion as assessed by the OGTT [2-4, 6, 7] or IVGTT [2,[4][5][6]. These studies reported that these gene variants were associated with reduced insulin secretion but not with insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, second-phase insulin secretion remained intact. Previously, several studies have investigated the effects of novel susceptibility loci on insulin secretion as assessed by the OGTT [2-4, 6, 7] or IVGTT [2,[4][5][6]. These studies reported that these gene variants were associated with reduced insulin secretion but not with insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Of these novel genes, FTO plays a role in childhood and adult obesity and the other five regions may play a role in pancreatic beta cell development and/or insulin secretion. Recent clinical results involving glucose tolerance tests indeed show that these variants affect insulin secretion, at least within the limitations of the tests used [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 98%
“…Participants The participants were selected from the ongoing Tübingen Family Study, which currently includes 2,000 individuals at increased risk of diabetes [4,8]. Less than 1% of participants are related to each other.…”
Section: Methodsmentioning
confidence: 99%
“…Impaired insulin secretion and impaired insulin sensitivity are the major pathogenic mechanisms leading to type 2 diabetes. Several of these novel risk loci for type 2 diabetes have been found to be associated mainly with impaired beta cell function [4][5][6][7][8]. Furthermore, a recently published study found associations between single nucleotide polymorphisms (SNPs) in TCF7L2 and increased fasting proinsulin concentration, suggesting that, in addition to insulin secretion, variation in TCF7L2 might be involved in insulin synthesis and processing [9].…”
Section: Introductionmentioning
confidence: 99%
“…Many of the confirmed type 2 diabetes variants have since been shown in population cohorts to alter beta cell function [7][8][9][10][11][12][13]. These studies include the RISC (Relationship between Insulin Sensitivity and Cardiovascular Disease) study [14], where we previously showed that CDKAL1 (rs10946398) and HHEX/IDE (rs1111875) loci were associated with altered beta cell function as measured by the 30 min insulin response and pancreatic beta cell glucose sensitivity derived from an OGTT [10].…”
mentioning
confidence: 99%